Analysis of The Concept of Green Legislation on Draft Regulation on Groundwater Conservation and Biopore Infiltration Holes in Cirebon City in 2024 - Yusup Permana, Deni; Dikrurahman, Diky; Wiranata, Fahad; Anggara, Adi; Karmenita, Karmenita; Gunawan, M. Sigit (Jurnal Legisci, 2025)
Background. Aim. This study aims to analyze the application of the concept of Green Legislation to the Draft Regional Regulation (Raperda) on Groundwater Conservation and Biopore Infiltration Holes in Cirebon City in 2024 Methods. This research uses a normative juridical method, which focuses on studying legal doctrines, legal principles, and regulations relevant to the research topic. Result. Based on an analysis of the 2024 Cirebon City Groundwater Conservation and Biopore Infiltration Hole Draft Regulation, it was found that a number of Green Legislation principles have been implemented, reflecting sustainability, wise management of natural resources, and environmental protection. The analysis results show that this draft regulation has included several principles of Green Legislation, such as regulations regarding water conservation and bio-pore management. However, there are gaps in implementation that need to be corrected. Conclusion. Therefore, the Cirebon City Government needs to improve the quality of the preparation of the Regional Regulation on Groundwater Conservation and Biopore Infiltration Holes by strengthening the integration of Green Legislation principles, especially aspects of sustainability, community participation, and wise management of natural resources. This effort can start by clarifying technical standards for constructing infiltration pits, improving the supervision and law enforcement system, and involving the community in socialization and policy implementation. Implication. Harmonization is needed between this Raperda and national policies such as the Job Creation Law to minimize the potential for regulatory conflicts and achieve the goal of preserving groundwater resources effectively and consistent with the principles of sustainable development.